2015
DOI: 10.1007/s00508-015-0718-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various factors on functional dyspepsia

Abstract: Aim of the research is to establish the prevalence of dyspepsia in Osječko-baranjska County, to establish its specific characteristics and to determine the effect of demographic, anthropometric, and socioeconomic factors. It is a cross-sectional and case control study conducted in 2010 on systematic sample of 900 subjects between 20 and 69 years of age. Every subject was sent an invitation letter and a Rome III diagnostic questionnaire for one of the disorders. A scoring algorithm was used to confirm or exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Table 2 shows how the pooled prevalence varied on the basis of the method used to define the presence of uninvestigated dyspepsia. When the validated Rome questionnaire was used, the highest prevalence was found in 23 studies that used the Rome III criteria (11.4%; 95% CI 9.4%-13.5%), 48,[62][63][64][65][66][68][69][70][71][73][74][75][76][77][79][80][81][83][84][85][86][87] while the prevalence was lowest in three studies using the Rome I criteria (5.2%; 95% CI 2.5%-8.8%). 26,33,60 Among the studies that approximated the Rome criteria using another questionnaire, the prevalence was highest when the Rome I criteria were used in 10 studies (22.6%; 95% CI 15.8%-30.3%), 27,28,30,31,35,38,39,42,43,51 while it was lowest in 11 studies using the Rome III criteria (11.8%; 95% CI 7.7%-16.7%).…”
Section: Prevalence Of Uninvestigated Dyspepsia According To the Ques...mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows how the pooled prevalence varied on the basis of the method used to define the presence of uninvestigated dyspepsia. When the validated Rome questionnaire was used, the highest prevalence was found in 23 studies that used the Rome III criteria (11.4%; 95% CI 9.4%-13.5%), 48,[62][63][64][65][66][68][69][70][71][73][74][75][76][77][79][80][81][83][84][85][86][87] while the prevalence was lowest in three studies using the Rome I criteria (5.2%; 95% CI 2.5%-8.8%). 26,33,60 Among the studies that approximated the Rome criteria using another questionnaire, the prevalence was highest when the Rome I criteria were used in 10 studies (22.6%; 95% CI 15.8%-30.3%), 27,28,30,31,35,38,39,42,43,51 while it was lowest in 11 studies using the Rome III criteria (11.8%; 95% CI 7.7%-16.7%).…”
Section: Prevalence Of Uninvestigated Dyspepsia According To the Ques...mentioning
confidence: 99%
“…eight32,36,37,46,52,53,56,61 and 16 studies34,48,57,58,62,63,47,[70][71][72][74][75][76]78,79,86 using the Rome I, II, or III criteria respectively. TwoBarberio et al …”
mentioning
confidence: 99%
“…Several studies reported that BMI including obesity positively associated with dyspepsia symptoms mainly in Europe, the United States, and Latin American countries. [11][12][13][14][15][16] In a large 10-year population-based study in Iceland, weight loss positively associated with the development of FD. 5 In other studies, no association between BMI and FD was found.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the development of intelligent drilling systems, domestic and foreign research scholars have done a lot of research on the bottom drilling tool combination analysis. In terms of theoretical research, Ebling et al [5] studied the in uence of rotation orientation factors on the yawing force of the bit and proved that the drilling pressure on the yawing force of the bit was not signi cant. e weighted residual rule of Gao [6] is to improve the calculation accuracy and reduce the workload.…”
Section: Introductionmentioning
confidence: 99%